Design, Synthesis and Biological Evaluation of New Substituted Sulfonamide Tetrazole Derivatives as Antitubercular Agents. Issue 8 (9th June 2016) - Suresh, Amaroju; Suresh, Narva; Misra, Sunil; Kumar, Muthyala Murali Krishna; Sekhar, Kondapalli Venkata Gowri Chandra
Abstract: The 1, 2, 4 triazole and tetrazole pharmacophore is still considered a viable lead structure for the synthesis of more efficacious and broad spectrum anti‐microbial agents. In this communication, a new class of highly potent anti‐tuberculosis agents are reported. Designed and synthesized a series of 18 compounds and evaluated them for their anti‐tubercular activity against Mycobacterium tuberculosis H37Rv strain. Among the compounds tested, five compounds exhibited moderate anti‐TB activity (MIC = 6.25 µg/mL); compounds8a, 8d, 8i, 9b and9f displayed good activity (Minimal inhibition concentration (MIC) = 3.12 µg/mL), while compounds8e, 8g, 8h, 9d and9h exhibited excellent activity (MIC = 1.56 µg/mL) against the growth of Mycobacterium tuberculosis H37Rv. Furthermore, they displayed no toxicity against CHO‐K1 cell lines at a concentration of 100 µM. These investigated analogues have emerged as potential leads to extend the scope of the anti‐tubercular research. Additionally, the most active compounds were docked to enzyme MTB CytP51 (2CIB.pdb) to understand ligand‐receptor binding interactions. Abstract : 18 tetrazole derivatives were screened against MTB H37Rv. Five compounds 8e, 8g, 8h, 9d and 9h exhibited excellent activity (MIC = 1.56 µg/mL). Compounds were non‐toxic against CHO‐K1 cells and were docked to MTB CytP51 enzyme for knowing binding interactions.